BIT CHECK IN ERROR DETECTION ON TEXT DATA TRANSMISSION USING HAMMING CODE ALGORITHM - Pilipus Tarigan (Sean Institute, 2021)
When data or information is transmitted via wireless or via cable channels, errors may occur while the data is transmitted. One of the efforts made is to apply error control coding. Hamming code is an example of an existing error control coding technique. Hamming code performance is distinguished by the number of parity bits it has. Ontelecommunications allows everyone to communicate with each other quickly over long distances though. Data that is transmitted or sent in the form of text data can fail (error). Errors cause changes in the contents of the data transferred to the recipient (Receiver) to change or fail. One way to detect simple errors is to use Hamming Code with single error correction. In the detection, this algorithm uses the EX-OR (Exclusive–OR) operation in the error detection process.In testing the data sent is not the same as the result received, the bit has experienced an error, and the system will correct the position where the bit has an error.